2021
DOI: 10.3390/ma14082057
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bioproducts Derived from Mixed Microbial Cultures Grown with Crude Glycerol to Protect Recycled Concrete Surfaces

Abstract: The large increase in the world population has resulted in a very large amount of construction waste, as well as a large amount of waste glycerol from transesterification reactions of acyl glycerides from oils and fats, in particular from the production of biodiesel. Only a limited percentage of these two residues are recycled, which generates a large management problem worldwide. For that reason, in this study, we used crude glycerol as a carbon source to cultivate polyhydroxyalkanoates (PHA)-producing mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…The results showed that the amount of water absorbed increased with the time of contact with water, reaching a constant mass after 96 h. Both bioproducts decreased the amount of water absorbed, by more than 17% for SP and by almost 8% for SG compared to water-treated specimens. These results were very similar to those obtained when using a MMC–glycerol-based concrete treatment [ 29 ], with improvements of 20% with SG and 13% with NSG (non-sonicated glycerol) and less than the 40% reduction, as found by Chandra et al [ 72 ], using cactus extract impregnated in concrete. Moreover, the results obtained with the SP treatment were similar to the ones reported by Oliveira et al [ 41 ] when MMC cultivated with the same carbon substrate was applied in air lime mortars, obtaining a reduction of 17% in water absorption.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The results showed that the amount of water absorbed increased with the time of contact with water, reaching a constant mass after 96 h. Both bioproducts decreased the amount of water absorbed, by more than 17% for SP and by almost 8% for SG compared to water-treated specimens. These results were very similar to those obtained when using a MMC–glycerol-based concrete treatment [ 29 ], with improvements of 20% with SG and 13% with NSG (non-sonicated glycerol) and less than the 40% reduction, as found by Chandra et al [ 72 ], using cactus extract impregnated in concrete. Moreover, the results obtained with the SP treatment were similar to the ones reported by Oliveira et al [ 41 ] when MMC cultivated with the same carbon substrate was applied in air lime mortars, obtaining a reduction of 17% in water absorption.…”
Section: Resultssupporting
confidence: 87%
“…This may have been due to the fact that SP had a more homogeneous distribution than SG over the treated surfaces, as can be seen in SEM images ( Figure 9 ) [ 29 , 67 ] taken after the assays. The better distribution of the SP biotreatment may have been due to its lower viscosity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations